Tomographic reconstruction strategies for nondestructive testing with a commercial CT scanner - Di Schiavi Trotta, Leonardo; Matenine, Dmitri; Lemaréchal, Yannick; Martini, Margherita; Stierstorfer, Karl; des Roches, Mathieu; Letellier, Philippe; Francus, Pierre; Després, Philippe (Frontiers in Earth Science, 2023)
In this work, a framework was developed to access and process raw data from a commercial X-ray Computed Tomography (CT) scanner for research purposes. Our method requires vendorprovided binaries to convert the data to a readable format and also to remove the effect of proprietary beam hardening preprocessing. As a result, custom reconstruction techniques, including beam-hardening corrections algorithms, can be applied. Small region-of-interest CT imaging techniques and different backprojection algorithms were investigated to improve image quality (spatial resolution, noise) with an in-house iterative reconstruction algorithm. For a reconstruction matrix of 512 pixels × 512 pixels, processing times of approximately 2.5 s per slice were obtained using a set of 8 x GPUs. With this framework, high-quality images of high density samples (e.g. minerals) can be obtained with reduced truncation-induced blurring, free of artifacts stemming from the reconstruction process and reduced beam-hardening artifacts.